If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x(x + y) = 20 + 3x (x * -5x + y * -5x) = 20 + 3x Reorder the terms: (-5xy + -5x2) = 20 + 3x (-5xy + -5x2) = 20 + 3x Solving -5xy + -5x2 = 20 + 3x Solving for variable 'x'. Reorder the terms: -20 + -3x + -5xy + -5x2 = 20 + 3x + -20 + -3x Reorder the terms: -20 + -3x + -5xy + -5x2 = 20 + -20 + 3x + -3x Combine like terms: 20 + -20 = 0 -20 + -3x + -5xy + -5x2 = 0 + 3x + -3x -20 + -3x + -5xy + -5x2 = 3x + -3x Combine like terms: 3x + -3x = 0 -20 + -3x + -5xy + -5x2 = 0 Factor out the Greatest Common Factor (GCF), '-1'. -1(20 + 3x + 5xy + 5x2) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(20 + 3x + 5xy + 5x2)' equal to zero and attempt to solve: Simplifying 20 + 3x + 5xy + 5x2 = 0 Solving 20 + 3x + 5xy + 5x2 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 5-7=d | | 4(3x-2)+5x=6(2x+8)-12 | | 3*(x-5)=15 | | y=144x^3-25x | | 4(n+5)+(n+7)=54 | | 49=t+16 | | (3z-2)(3z+8)=(z-4)(z+4) | | 2y+6+10=18-2y | | -11+r=37 | | (2COSx+1)sinx=0 | | (3z-2)(3z+8)= | | 8+x=13+12x | | 7(a+5)=84 | | 11x^2-31x-54=0 | | 2m+r=28 | | 36x^2=180 | | 2x^2+2x+140=180 | | 14n+2=5n+65 | | -3(w+5-10)=2w+5 | | s+s=900 | | 3x+8x=36 | | 6m-24=30 | | 9x-(3x+8)=7x-12 | | a+(a+2)=10 | | X-5y-20=0 | | 40+16x+4=23x+2 | | (13x+45)+(12x-40)=180 | | 175+(17x-3)=17x+8 | | 75+30h=75+45h | | y=15-12.7272727273/4 | | .3*x=63 | | 8x-25=6x+9 |